Can Good Corporate Governance Moderate the Relationship Between Earnings Management and Firm Value? - Adriyani Karianga; Frisky Jeremy Kasingku (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to empirically examine the impact of earnings management toward firm value, the impact of good corporate governance toward firm value, and the impact of good corporate governance as a moderating variable on the relationship between earnings management and firm value. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019 which were selected using the purposive sampling method, 81 companies fulfilled the sampling method requirement and were used as the sample for this study. To test the hypothesis, simple and multiple linear regression were conducted. The research results proved that earnings management measures do not have a significant effect on firm value. Furthermore, simultaneously, good corporate governance has a significant effect on firm value. Partially, one of the components of good corporate governance which is audit quality, was proved statistically to have a significant effect on firm value. In contrast, good corporate governance was not able to moderate the relationship between earnings management and firm value.